O fundamento das improbidades na administração pública municipal brasileira - Vieira, James Batista (2013)
Throughout history, few phenomena aroused so much interest among citizens and wasted so many resources of the State and contributed so much to the delay in its development as the problem of "corruption of public agents." In this thesis, I use the concept of improbity to define a particular type of phenomenon and distinguish it from others usually covered by reference to corruption. Thereafter I try to answer the following questions: what elements influence the decision-making process of the public agent to consider engaging in an improbity? What factors are associated with the occurrence of improbity in Brazilian local public administration? From the perspective of new institutional economics, the first part of the thesis proceeds with the conceptual and methodological analysis of the phenomenon, embodied in the analytical framework of improbity, arguing that: a) the improbity correspond to a kind of opportunistic attitudes, among which stands out a species called corrupt transaction b) the decision-making process of the public agent, placed in the context of bounded rationality, is equally oriented by elements of cost-benefit analysis (maximization of expected utility), the dynamics of learning processes and their own ethical and moral barrier. Other parts of this thesis present the results of a systematic empirical investigation, based on information from a random sample of 960 municipalities audited by the General Controller Office. The analysis highlights the factors associated with the occurrence of improbity, both from the point of view of the traditional literature (modernization, social capital and rent-seeking), as the new analytical perspective proposed, based on governance mechanisms. The test from the traditional models of literature demonstrates: a) the negative association between the occurrence of improbity and indicators of institutional performance and socioeconomic development of the municipalities (in accordance with the effects commonly assigned to improbity), b) the negative association between the occurrence of improbity and indicators of modernization and social capital of the municipalities (in line with the causes commonly granted to improbity), c) the lack of association between the occurrence of improbity in Brazilian municipalities and indicators to encourage rent-seeker behavior (as opposed to the classical proposition that the greater the size of the State, the greater the occurrence of improbity because of incentives arising from its monopoly). Based on these findings, I have integrated the new institutionalism assumptions to the analysis of the improbity, interpreting them as failures of governance structures. Thus, beyond the impact of institutional arrangement that encompass the legislative control, administrative and judicial review of internal and external resources that Brazilian federal government transferred to municipalities, I have present evidences that the observed variations in the count of improbity in Brazilian municipalities are directly related to the quality of its governance arrangements. Among these, stand out from those of democratic nature like the mechanisms of social control (municipal councils of public policy); mechanisms for promoting transparency (the quality of e-government), and the accountability mechanism (the electoral dispute). According to the analytical framework of improbity, the existence and operation of these mechanisms raise the transaction costs of the public agents, even surpassing the limitations of ethical-moral barrier and learning.